An Empirical Study on Customer Satisfaction, Perception, and Brand Image in Starbucks Coffee in India, Asia - Pandey, Rudresh; Ganatra, Varsha; Jamnik, Sonali; Goel, Pragya; Goyal, Priyanshi; Xuan, Chian Lee; Kee, Daisy Mui Hung; Mein, Hee Hui; En, Lim Xiao; Zen, Lee Jen (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
This study focuses on the brand image, experience, quality, and services offered by Starbucks that will bring customer loyalty from customer satisfaction. The study analyzes how customer loyalty and brand experience affect the quality improvements of Starbucks Coffee as corporate brands play a vital role in achieving higher company’s performance, like sales. It makes more incentives to satisfy the potential customers and develops a drawn-out relationship with them. This study concludes that companies with higher customer loyalty and satisfaction tend to have higher market share, and move further by cost reduction. Therefore, companies could substantially pay attention to all of these variables to have an everlasting profitability as this will lead to gain competitive advantage in the market.